'Small sees big': international order through small state leaders' insights via the intellectual propaganda of Czechoslovak, Ghanaian and Singaporean leaders. Issue 2 (4th May 2021) - Chong, Alan
ABSTRACT: The study of small state perceptions of international order has been much neglected. Small state leaders are intellectual heavyweights in a disproportionate relationship to their respective sovereign territorial domains. To navigate the treacherous currents of international order, they rely on their own synthesised views of manoeuvrable spaces amongst great powers. Simultaneously, they are also reflective of the limits of global institutional governance. Moreover, small state leaders frequently weigh international order in moral terms. The intellectual propaganda of charismatic and authoritative foreign policy leaders from then-Czechoslovakia, Ghana and Singapore will be read to illustrate these insights. The conclusion will suggest that small state theorising can enrich mainstream IR theory as a result of these perspectives from small state actorness.